PERENCANAAN DAN PENGEMBANGAN DESA WISATA BERBASIS MASYARAKAT DENGAN MODEL PARTISIPATORY RURAL APPRAISAL (STUDI PERENCANAAN DESA WISATA GUNUNGSARI, KECAMATAN BUMIAJI, KOTA BATU) - Mohamad Nur Singgih; Nirwana Nirwana (Jurnal Pariwisata Pesona, 2016)
Soetomo (2007), tourism development efforts which is local society oriented is still low and there are a lot of development failure because the policy holder still think partially. They only think about institution and sectorasl ego; society considered do not have the financial ability and quality skill to manage or participated directly in tourism nature and culture based activities.The aim of this research is 1) arrange the tourism rural activity area based on society sustainability tourism development. 2) Mapping the potentials, necessity and issues to plan the rural tourism development. 3) Empowering the societyto be responsible and play an active role toward planning and managing the rural tourism. This research is using qualitative descriptive with its variable rural tourism developmant plan. The data were collected by using observation, interview, documentation, and directional group discussion. The data analysis method is using appraisal rural partisipatory method consist of village history, seasonal calendar, daily lifes, village map, transect, livelihood analysis, and matrix ranking.